2018
DOI: 10.1111/2041-210x.13063
|View full text |Cite
|
Sign up to set email alerts
|

Testing the potential of Twitter mining methods for data acquisition: Evaluating novel opportunities for ecological research in multiple taxa

Abstract: Social media provides unique opportunities for data collection. Retrospective analysis of social media posts has been used in seismology, political science and public risk perception studies but has not been used extensively in ecological research. There is currently no assessment of whether such data are valid and robust in ecological contexts. We used “Twitter mining” methods to search Twitter (a microblogging site) for terms relevant to three nationwide UK ecological phenomena: winged ant emergence; autumna… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
20
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(21 citation statements)
references
References 29 publications
1
20
0
Order By: Relevance
“…Also, in order to reduce illegal trafficking, it has been suggested to use deep learning algorithms to monitor such activities on social media to automatically detect pictures of illegal wildlife products (Di Minin, Fink, Tenkanen, & Hiippala, ). Using deep learning for data mining could easily be extended to other areas, as social media mining has proven to be useful for ecological research such as phenological studies (Hart, Carpenter, Hlustik‐Smith, Reed, & Goodenough, ).…”
Section: Overview Of Applications In Ecologymentioning
confidence: 99%
“…Also, in order to reduce illegal trafficking, it has been suggested to use deep learning algorithms to monitor such activities on social media to automatically detect pictures of illegal wildlife products (Di Minin, Fink, Tenkanen, & Hiippala, ). Using deep learning for data mining could easily be extended to other areas, as social media mining has proven to be useful for ecological research such as phenological studies (Hart, Carpenter, Hlustik‐Smith, Reed, & Goodenough, ).…”
Section: Overview Of Applications In Ecologymentioning
confidence: 99%
“…The use of social media to gather relevant data on biological and ecological issues is likely to increase in the future (e.g. Hart et al, 2018).…”
Section: Namementioning
confidence: 99%
“…This showcases the potential of using voluminous search engine data to explore species distributions in many regions. Others have explored species occurrences and distributions using various sources, such as Flickr, news articles, Twitter, YouTube, Facebook, and Google Trends [13][14][15][16][17][18][19][20][21][22][23][24][25], as well as population dynamics and phenology [14,20,23,[26][27][28][29][30][31]. A particular illustration comes from assessing seasonal migration patterns of sockeye salmon (Oncorhynchus nerka) and Atlantic salmon (Salmo salar) from Wikipedia pageview frequencies (Figure 2B) [32].…”
Section: Research Scopementioning
confidence: 99%
“…The vast majority of iEcology studies that we have identified have used multiple data sources to validate results, including data from field research, citizen science, online databases, scientific literature, or their combination [12,13,[16][17][18][19][20][21][22][23][24][25]31,32,35,43,44]. In most cases, authors report a satisfying to excellent level of consistency among data sources.…”
Section: Web Scrapingmentioning
confidence: 99%